Intellectual Property and Regional Trade in the Southern African Development Community - Hakizimana, Nadine (My University, 2019)
This study assesses efforts to mainstream intellectual property rights (IPR) in international trade. A review of the literature reveals that the linkage of intellectual property (IP) to trade is part of a broad agenda initiated by the World Trade Organization (WTO) and several developed countries to control economic markets. This international IP harmonization agenda allows developed countries to maintain market power through strict intellectual property protection. The IP-trade linkage exposes the asymmetries between developed and developing countries. This dynamic is explored through a case study of the Southern African Development community (SADC) which reveals that although IP was not a priority to the regional economic community (REC) at the time it was created, IP has since become an important part of the SADC regional agenda. As such the SADC have aligned to the international IP harmonization agenda. The study considers what some of the push and pull factors are that determine the accession of SADC to the international IP system. Discussions on the disincentives for IPR in SADC are mostly based on evidence of the adverse implications IPR have in developing and least developed countries. Based on this evidence, there has been some resistance to IP protection by SADC states, in line with the attitude of developing countries across the world. Accordingly, African countries, have made efforts to deviate from the prevailing IP system through the establishment of structures like the African Regional Intellectual Property Organization and Pan African Intellectual Property Organization, as well as the refusal of some countries to sign treaties that are not applicable to their economic realities. However, these approaches inevitably come into contact with international pressures from the TRIPS-enforcement mechanism and free-trade agreements with developed countries that carry IP-related pre-conditions to trade. The findings show that consequences to international pressure for IP harmonization are often revealed in small nuances of IP-related policy decisions that are not always voluntary.
Intellectual property and regional trade in the Southern African Development Community
A research report submitted in partial fulfilment of the requirement for the degree of Master of Arts by Creative Writing to the Faculty of Humanities, University of the Witwatersrand, 2019
Keywords: Intellectual property--Africa, Southern.